Star-polymer–colloid mixtures - Dzubiella, J.; Jusufi, A. (Condensed Matter Physics, 2002)
Recent results in theory and simulation of star-polymer–colloid mixtures are reviewed. We present the effective interaction between hard, colloidal particles and star polymers in a good solvent derived by monomer-resolved Molecular Dynamics simulations and theoretical arguments. The relevant parameters are the size ratio q between the stars and the colloids, as well as the number of polymeric arms f (functionality) attached to the common center of the star. By covering a wide range of q ’s ranging from zero (star against a flat wall) up to about 0.5, we establish analytical forms for the star-colloid interaction which are in excellent agreement with simulation results. By employing this cross interaction and the effective interactions between stars and colloids themselves, a demixing transition in the fluid phase is observed and systematically investigated for different arm numbers and size ratios. The demixing binodals are compared with experimental observations and found to be consistent. Furthermore, we map the full two-component system on an effective one-component description for the colloids, by inverting the two-component Ornstein-Zernike equations. Some recent results for the depletion interaction and freezing transitions are shown.